Analisis Pesan Propaganda selama Pilpres 2024 di X - Pambudi, Buyung; Prajarto, Nunung; Irawanto, Budi (Jurnal Media dan Komunikasi Indonesia, 2025)
Propaganda messages disseminated using digital technology are part of the elements of political propaganda as a communication event. On the one hand, propaganda messages are a means of conveying messages aimed at maintaining a good image of the candidate being supported. On the other hand, propaganda messages are directed at bringing down the image of opposing candidates. Digital propaganda messages can be sorted into three categories, namely disinformation, malinformation, and misinformation. Propaganda messages can be seen by observing certain topics related to politics during general elections, especially the 2024 presidential election. Topics that were discussed by netizens on X during the 2024 presidential election became a means to spread propaganda messages either aimed at supporting certain candidates or attacking opposing candidates. During the 2024 presidential election in Indonesia, propaganda messages were widely spread on social media, including on X, which used to be called Twitter. All candidates in the 2024 presidential election could not avoid propaganda attacks with the aim of bringing down their image. The 2024 presidential election shows that netizens in X are not as divided as Cebong and Kampret in the 2019 presidential election. Therefore, propaganda messages are directed more towards the candidates rather than the candidates' supporters. Propaganda messages spread on X can be in the form of narrative sentences, images, videos, and audio. There are even propaganda messages created with the help of artificial intelligence technology. The use of artificial intelligence technology is new in propaganda during the presidential election in Indonesia.